Association of leukemia inhibitory factor gene polymorphism and in vitro fertilization outcome in a population in northern Iran - Alipour, M.; Mashayekhi, F.; Salehi, Z. (Cellular and Molecular Biology, 2017)
Several studies have been demonstrated that endometrial leukemia inhibitory factor (LIF) is important in embryo implantation. LIF is a secreted glycoprotein with a variety of biological functions including stimulation of cell proliferation, differentiation and survival that are all essential for blastocyete development and implantation. The LIF receptor activates several signaling pathways in diverse cell types, including Jak/STAT, MAPK and PI3-kinase pathways in the endometrium of fertile woman. It has been suggested that the initial lower expression of LIF in proliferative phase may be one of the causes for multiple failure of implantation. The aim of this study was to evaluate the association between maternal genotype of SNP 3951C/T LIF and in vitro fertilization and embryo transfer (IVF-ET) outcome in infertile women. This case–control study was comprised of infertile patients (n=70) and women having one healthy child as controls (n=73). Genotyping for SNP-3951C/T was performed by PCR/RFLP. Allele and genotype distribution did not differ significantly between patients and controls (P>0.05). The LIF genotype frequencies amongst the 70 cases were C/C=40%, C/T=52.8% and T/T=7.2%; the C and T allele frequencies were 66% and 34%, respectively. The LIF genotype frequencies amongst the 73 controls were C/C=45.20%, C/T=50.70% and T/T=4.1%; the C and T allele frequencies were 70% and 30%, respectively. In conclusion, the results of this study indicate that SNP 3951C/T of LIF may not be associated with IVF-ET outcome in this population. Although more studies should be considered with larger number of patients and control subjects to confirm our results.